Additive Differential Pulse Voltammetry for the Study of Slow Charge Transfer Processes at Spherical Electrodes - Laborda, E; Rogers, E; Martinez-Ortiz, F; Molina, A; Compton, R (2010)
The application of additive differential pulse voltammetry to the study of the kinetics of a charge transfer process is studied. A simple analytical solution is presented, valid for spherical electrodes of any size and for electrode processes of any reversibility. From this solution, valuable diagnostic criteria for the elucidation of the electrochemical reversibility are established based on the variation of the ADPV signal with the duration of the potential pulses, the electrode radius and the pulse height. Working curves for the determination of the kinetic parameters are also given. The value of the ADPV technique is experimentally demonstrated by studying the kinetics of the reduction of 3-nitrophenolate- and europium3+ at mercury hemispherical microelectrodes. © 2010 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.